Biology and Application of Chaetomium globosum as a Biocontrol Agent: Current Status and Future Prospects - Shailja Sharma; Saurabh Pandey; Sourabh Kulshreshtha; Mukesh Dubey (Microorganisms)
Chaetomium globosum is a widely distributed fungal species recognized for its ability to produce a range of secondary metabolites. This fungus plays a significant ecological role by degrading organic matter and contributing to nutrient cycling in diverse ecosystems. In recent years, C. globosum has attracted considerable scientific interest due to its potential as a biocontrol agent [BCA] against a wide array of diseases in numerous plant species. While the precise mechanisms of C. globosum as a BCA remain poorly understood, interference competition through antibiosis is one of the key mechanisms. Moreover, C. globosum can enhance plant health by promoting nutrient availability, manipulating the rhizosphere microbiome, and inducing plant defense responses. The formulation of C. globosum for agricultural applications has been reported, which can significantly improve stability and efficacy under field conditions. However, despite significant advancements in omics and molecular biology technologies, the biology of C. globosum is understudied. Enhanced research into the genetics and functional genomics of C. globosum could pave the way for its applications in sustainable agriculture. This review summarizes the role of C. globosum as a BCA, focusing on its underlying mechanisms such as genomics and transcriptomics, and the effects of C. globosum application on soil health and the rhizosphere microbiome.